Effect of depressive symptoms on quality of work life in female nurses: a cross-sectional study using propensity score matching - Li, Jia-Ning; Chen, Xiao-Qian; Li, Qing-Qing; Zheng, Qing-Xiang; Pan, Yu-Qing; Huang, Ling; Zhu, Yu; Liu, Ru-Lin; Jiang, Xiu-Min (Frontiers in Psychiatry, 2023)
Background: Female nurses have been considered as a vulnerable population in the context of mental health, due to the nature of their work, which can be stressful and emotionally taxing. Understanding the relationship between depressive symptoms and quality of work life (QWL) can contribute to improving mental health and job performance. However, limited studies have focused on the effect of depressive symptoms on QWL in female nurses.The present study aimed to assess the effect of depressive symptoms on female nurses' QWL using propensity score matching (PSM).Methods: A cross-sectional, online study using convenience sampling was conducted among 1401 female nurses in China. PSM was used to minimize the impact of potential confounders between no depressive symptoms and depressive symptoms. Stepwise multiple linear regression analyses were performed on the PSM samples to explore the effects of depressive symptoms on the QWL.The results revealed there were 33.5% of the female nurses reported depressive symptoms before PSM. And female nurses in this study had a moderate level of QWL before PSM (122.11±18.15), which remained steady after PSM (118.33±18.04). After PSM, the final sample contained 864 female nurses. Stepwise multiple linear regression results indicated that depressive symptoms were the strongest factor associated with QWL (β = -0.454, P < 0.001).This study highlights the importance of developing mental health plans and psychological interventions for female nurses to maintain mental health and QWL, which is critical to the nursing workforce's sustainability.